Experimental and numerical research on the influence of steel arch frame corrosion on security of supporting system in subsea tunnel. (February 2022) - Zhang, Yiteng; Wang, Mingnian; Yu, Li; Guo, Xiaohan; Wang, Zhuhong; Li, Chunhui
Highlights: The bond-slip behavior and characteristics between corroded I-shaped steel and concrete was conducted. A new bond-slip degradation model between corroded I-shaped steel and concrete was developed based on interface damage. The bond-slip constitutive was applied to security analysis of tunnel supporting system. When the corrosion rate reaches 70%, the stress of I-shaped steel reaches its own yield strength. The safety factor of sprayed concrete/secondary lining concrete has been reduced owing to I-shaped steel corrosion. Abstract: Subjected to high chloride ion content in subsea, underwater structure will be corroded in different degree in the service environment, which will shorten the durability of the structure. Subsea tunnels are often constructed by drilling and blasting method, and microcracks are inevitable in primary support due to blasting impact. The cracks provide channels for chloride ion, sulfate ion in seawater and oxygen in air, which leads to steel arch frame corrosion in primary support. Corrosion will reduce the bond strength and bearing capacity of the supporting system, thus reducing the service time of the subsea tunnel. Based on Xiang'an subsea tunnel, the effect of steel arch frame corrosion on the supporting system was studied. First, the accelerated corrosion test and push-out test were carried out, the bond-slip degradation constitutive model between corroded I-shaped steel and concrete was proposed based on damage variables. Then, the degradation constitutive model was introduced into ANSYS to simulate the influence of corroded I-shaped steel on the overall mechanical behavior and safety of the subsea tunnel. Results of model indicated that with the increase of corrosion ratio, the internal stress of the I-shaped steel, sprayed concrete and secondary lining increased, and the corresponding safety factors all decreased.